Pelaksanaan Pemenuhan Hak Narapidana Anak Dalam Rangka Perlindungan Anak Di LPKA Kelas II Yogyakarta - Endang Heriyani; Prihati Yuniarlin (Universitas Labuhanbatu, 2022)
The rights of children who are undergoing a criminal period have been regulated in Article 4 of Law Number 11 of 2012 concerning the Child Criminal Justice System (Child Justice Law). Child prisoners in LPKA are separated from their families, so their rights can be neglected. This research is normative empirical by collecting legal literature, looking for principles, doctrines and comparing the actual conditions that occur in society. The conclusion in this study is child prisoners living in LPKA Yogyakarta have obtained their rights as children, such as right of education, worship, develop themselves, and so on. LPKA's efforts to optimize the fulfillment of the rights of child prisoners in the context of child protection are collaborating with the Disdikpora of Gunungkidul Regency by forming an SKB (Study of Learning Activities), and the Ministry of Religion of Gunungkidul Regency to provide tutorials on religious lessons.Keywords:Â Rights of child prisoners, child protection